Quality and green management for operational and environmental performance: relational capital in supply chain management. Issue 4 (4th May 2022) - Wu, Rong; Huo, Baofeng; Yu, Yubing; Zhang, Zuopeng(Justin)
ABSTRACT: Based on the resource-based view and the social capital theory, this study investigates how quality management and green management in firms' supplier relational capital and customer relational capital in supply chains influence their operational performance and environmental performance. We collected data from 213 manufacturers to test the proposed relationships. The results show that quality management and green management play different roles in facilitating firms' operational performance and environmental performance. On the supplier relational capital side, quality management is the major driver of firms' operational performance and environmental performance, and quality management completely mediates the relationship between supplier relational capital and green management. On the customer relational capital side, green management improves firms' operational performance, and firms' operational performance completely mediates the relationship between quality management and environmental performance. This study provides managerial implications for firms to gain considerable operational performance and environmental performance by integrating quality management and green management.